Protection induced by an attenuated strain of Salmonella Typhimurium in guinea pigs - Changanaquí, Christian (2023)
The aim of this study was to evaluate the protective capacity of an attenuated strain of Salmonella Typhimurium as a vaccine candidate against an experimental challenge. For this purpose, 51 recently weaned female guinea pigs from a commercial farm were used and distributed into three groups of 17 animals each: one group was inoculated with the attenuated strain and challenged, the second group was challenged only, and the third group served as a control (without attenuated strain and without challenge). The animals, according to their respective groups, were immunized after two weeks of adaptation to the new rearing conditions. Five weeks after immunization they were challenged with a virulent strain of S. Typhimurium. The health status was monitored for five weeks post-challenge and fecal samples were collected to demonstrate the excretion of IgA and S. Typhimurium. Additionally, necropsies were performed on the animals that died as well as on the survivors at the end of the study. Organ samples for microbiological and histopathological evaluation were taken. No significant differences in survival rate and daily weight gain were observed between the challenged groups. However, at the level of lesions, a higher frequency of pneumonic foci and intestinal affections were observed in the group that was only challenged compared to the inoculated group with the attenuated and challenged strain (p<0.05).